Agile practices: A cognitive learning perspective - Omar, Mazni; Syed Abdullah, Sharifah Lailee (2013)
This paper highlights the theoretical aspect of agile practices from the cognitive learning perspective.Three cognitive strategies–elaboration, organization, and problem solving–underpin key strategies in agile practices to promote better understanding in learning software development activities. Agile practices such as planning games, pair programming, refactoring, coding standard and simple design, acts as a positive inducer to human brain for software developers to accept and develop software easily.By understanding theoretical aspects hinders in agile practices, educators are able to determine alternative approach to suit into internal potentials among students, and thus be able to develop high quality software.